Characterization and evaluation of a flexible MRI receive coil array for radiation therapy MR treatment planning using highly decoupled RF circuits. (13th April 2018) - McGee, Kiaran P; Stormont, Robert S; Lindsay, Scott A; Taracila, Victor; Savitskij, Dennis; Robb, Fraser; Witte, Robert J; Kaufmann, Timothy J; Huston, John; Riederer, Stephen J; Borisch, Eric A; Rossman, Phillip J
Abstract: The growth in the use of magnetic resonance imaging (MRI) data for radiation therapy (RT) treatment planning has been facilitated by scanner hardware and software advances that have enabled RT patients to be imaged in treatment position while providing morphologic and functional assessment of tumor volumes and surrounding normal tissues. Despite these advances, manufacturers have been slow to develop radiofrequency (RF) coils that closely follow the contour of a RT patient undergoing MR imaging. Instead, relatively large form surface coil arrays have been adapted from diagnostic imaging. These arrays can be challenging to place on, and in general do not conform to the patient's body habitus, resulting in sub optimal image quality. The purpose of this study is to report on the characterization of a new flexible and highly decoupled RF coil for use in MR imaging of RT patients. Coil performance was evaluated by performing signal-to-noise ratio (SNR) and noise correlation measurements using two coil (SNR) and four coil (noise correlation) element combinations as a function of coil overlap distance and comparing these values to those obtained using conventional coil elements. In vivo testing was performed in both normal volunteers and patients using a four and 16 element RF coil. Phantom experiments demonstrate the highly decoupled nature of the new coil elements when compared to conventional RF coils, while in vivo testing demonstrate that these coils can be integrated into extremely flexible and form fitting substrates that follow the exact contour of the patient. The new coil design addresses limitations imposed by traditional surface coil arrays and have the potential to significantly impact MR imaging for both diagnostic and RT applications.